Determination of criminal behavior of minors - Юзікова, Наталія Семенівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The current transition of society to the path of market economy is accompanied by the political and social conflicts, dysfunctionality of the major social institutions, destabilization of the economy, and as a result these all cause the growth of juvenile criminal activity. Causes of juvenile criminal behavior are connected with the functioning of social institutions. The article examines the political, economic, social, moral and psychological causes of juvenile delinquency. One of the causes of juvenile delinquency is the inability of the authorities and law enforcement agencies to carry out the task of combating crime effectively. The completion of reforms will respond to juvenile delinquency and optimize the usage of educational and preventive measures. Deformation of social institutions of society reflected in the living conditions of Ukrainian citizens: the number of unemployed has increased, well-being has decreased. These social causes influenced the level of criminal activity of minors. Especially this effect manifests in the commission of violent and selfish crimes. Media plays a single place in the determination of criminal behavior of juvenile. It has an influence on the formation of moral and psychological climate of juvenile . Thus, the observation of violence lays the skills and teaches child to view violent behavior. Teens learn this kind of behavior through the media and follow it. Causes, conditions, factors which determine the juvenile criminal behavior were analyzed in the article. They can be the basis of a set of measures and the national program for prevention juvenile delinquency. Preventive measures and comprehensive programs should be based on the performance of basic society functions of social institutions.